Are all Sex Criminals the Same? Consumers of Child Pornography Reconsidered - Vaisman-Tzachor, Reuben (Frontiers in Law, 2023)
A theoretical and practical distinction is drawn between sex offenders and consumers of child pornography on the bases of their unique and different psychological makeups and motives to offend. Distinct psychological profiles have been revealed in clinical practice and in research between “active” sex offenders (e.g., sexual assault, sexual abuse, molestation, active pedophiles, etc.) and “passive” sex offenders (i.e., those prosecuted for consumption of child pornography). Recommendations are made for legislation changes and development of treatment approaches, based on these differences.